1990
DOI: 10.1021/bi00459a040
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore topography and secondary structure of 124-kilodalton Avena phytochrome probed by zinc-induced chromophore modification

Abstract: The relative extent of chromophore exposure of the red-absorbing (Pr) and far-red-absorbing (Pfr) forms of 124-kDa oat phytochrome and the secondary structure of the phytochrome apoprotein have been investigated by using zinc-induced modification of the phytochrome chromophore. The absence of bleaching of Pr in the presence of a 1:1 stoichiometric ratio of zinc ions, in contrast to extensive spectral bleaching of the Pfr form, confirms previous reports of differential exposure of the Pfr chromophore relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
27
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
8
27
1
Order By: Relevance
“…Immediately after the end of the irradiation, 5 M HC1 was added to lower the pH to 9.0. The alkaline treatment at pH 11.0 yielded a stable bleached spectrum at pH 9.0 similar to those of soyasaponin-treated (Konomi et al, 1982), tryptic digestion-treated (Yamamoto & Furuya, 1983), and zinciontreated (Sommer & Song, 1990) phytochromes, although alkaline treatment lower than pH 11 .O showed reversion to PI at pH 9.0.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Immediately after the end of the irradiation, 5 M HC1 was added to lower the pH to 9.0. The alkaline treatment at pH 11.0 yielded a stable bleached spectrum at pH 9.0 similar to those of soyasaponin-treated (Konomi et al, 1982), tryptic digestion-treated (Yamamoto & Furuya, 1983), and zinciontreated (Sommer & Song, 1990) phytochromes, although alkaline treatment lower than pH 11 .O showed reversion to PI at pH 9.0.…”
mentioning
confidence: 74%
“…A model of Pbl was prepared by alkaline treatment, since the addition of bleaching reagents such as zinc ions (Sommer & Song, 1990) or soyasaponin (Konomi et al, 1982) to the highly concentrated phytochrome solutions induced some precipitation. In brief, large phytochrome precipitated with ammonium sulfate was resuspended in 50 mM CHES and 1 mM Na2EDTA at pH 9.0, and then its pH was raised to 11.0 by adding 5 M NaOH.…”
mentioning
confidence: 99%
“…The ratio of [θ] 190 /[θ] 220 values indicated that the predominant secondary structural component in all Cph1 proteins analyzed was the R-helical conformation (Table 2), as in plant phytochromes (33,34). The R-helical content of the apoprotein was calculated to be 37%.…”
Section: Expression and In Vitro Reconstitution Of The Cph1mentioning
confidence: 99%
“…A specific conformational change occurs along the amino terminal chain of phyA upon its phototransfonnation from the Pr to the Pfr form (Chai et al 1987;Vierstra et al 1987;Sommer & Song 1990). To test the reliability of the circular dichroism (CD) spectroscopy, three different CD analysis methods have been used to determine the secondary structure of pea phyA in both the Pr and the Pfr forms (Deforce et al 1994).…”
Section: Light-induced Conformational Changesmentioning
confidence: 99%
“…To test the reliability of the circular dichroism (CD) spectroscopy, three different CD analysis methods have been used to determine the secondary structure of pea phyA in both the Pr and the Pfr forms (Deforce et al 1994). We showed that the secondary structure of dicot pea phyA is very similar to that of monocot oat phyA (Sommer & Song 1990), interdependent of the method of CD analysis (Deforce et al 1994). As with oat phyA, an increase in a-helix of the apoprotein polypeptide takes place when the Pr form is phototransfonned to the Pfr form.…”
Section: Light-induced Conformational Changesmentioning
confidence: 99%